Number 37 (July 1998) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1998)
(July 1998) - Status of the ironcolor shiner, Notropis chalybaeus in Mississippi. By Brett Albanese and William T. Slack Morphometric, meristic, and natural history notes on Menidia beryllina and M. peninsulae in a marginal sympatric area in Perdido Bay, Alabama and Florida. By Royal D. Suttkus and Maurice F. Mettee
Keywords: ironcolor shiner; notropis chalybaeus; menidia beryllina; m. peninsulae; perdido bay